EVALUATION BEARING CAPACITY OF RING FOOTINGS ON REINFORCED LOOSE SAND - Fartosy, sabah hassan lafta; Jawad, Faris Waleed; Hacheem, Zuhair Abd; Al-Madhhachi, Abdul-Sahib T. (Journal of Applied Engineering Science, 2022)
Ring footing represents a significant structural member in different applications such as fuel or water storage tanks in addition to other structures. The advantage of this type of footing is related to the ability to reduce the weakness of some soils that may affect the safety of structures. An experimental testing program was conducted by using a small-scale model in the laboratory of the college of engineering at the university of Al-Mustansiriyah which consists of twelve ring footing models resting on loose sand reinforced by geogrid layers. The parameters that studied in this research are the diameter of ring footing, thickness of ring, the position placed of one reinforced layer and vertical spacing between two reinforced layers. The findings of this research shown that the optimum percentage of diameter ratio of ring footing is (0.25) and when the depth-ratio increases, the bearing-capacity of ring footing begin decreases. In general, the increase in ring thickness causes the bearing-capacity and the rigidity of ring foundation to increase. The optimum of the depth-ratio of the first reinforced layer is (0.25) and the optimum value of vertical-spacing bounded by layers is around (0.25) which produces a maximum value of the bearing-capacity. Its noticed that when these percentages exceeded value 0.25, the bearing-capacity of the ring foundation drops eventually.